Enzyme‐free Cu2O@MnO2/GCE for Hydrogen Peroxide Sensing. Issue 7 (5th April 2019) - Ouiram, Tik; Moonla, Chochanon; Preechaworapun, Anchana; Tangkuaram, Tanin
Abstract: A novel composite material of copper (I) oxide at manganese (IV) oxide (Cu2 O@MnO2 ), was synthesized and applied for modification on the glassy carbon electrode (GCE) surface (Cu2 O@MnO2 /GCE) as a hydrogen peroxide (H2 O2 ) sensor. The composite material was characterized regarding its structural and morphological properties, using field emission scanning electron microscopy (FE‐SEM), energy‐dispersive X‐ray spectroscopy (EDX), X‐ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The Cu2 O@MnO2 /GCE showed an excellent electrocatalytic response to the oxidation of H2 O2 which provided a 0.56 s −1 charge transfer rate constant ( K s ), 1.65×10 −5  cm 2  s −1 diffusion coefficient value ( D ), 0.12 mm 2 electroactive surface area ( A e ) and 1.04×10 −8  mol cm −2 surface concentration ( γ ). At the optimal condition, the constructed sensor exhibited a wide linear range from 0.5 μM to 20 mM with a low limit of detection (63 nM, (S/N=3) and a good sensitivity of 256.33 μA mM −1  cm −2 . It also presented high stability (ΔIresponse ±15 %, n=100), repeatability (1.25 %RSD, n=10) and reproducibility (3.55 %RSD, n=10). The results indicated that the synthesized Cu2 O@MnO2 was successfully used as a new platform for H2 O2 sensing. Abstract :